KETERKAITAN STRUKTUR KELUARGA DENGAN PERKEMBANGAN PSIKOLOGIS DAN ORIENTASI KARIER REMAJA AWAL - Cynthia Petra Haumahu; Theophanny P. Th. Rampisela (CV. ADIBA AISHA AMIRA, 2025)
This study aims to explore the relationship between family structure, psychological development, and career orientation among early adolescents at the junior high school level. Family structure is considered one of the main social factors that influence identity formation, career efficacy, and emotional maturity in adolescents. The approach used was qualitative phenomenological, with 12 participants (6 from intact families and 6 from broken homes) in Bandung City. Data were collected through semi-structured interviews and field observations, then analysed using reflective thematic analysis. The results showed that family emotional support, open communication, and parenting stability played an important role in shaping adolescents' emotional regulation and career orientation. Students from intact families showed higher levels of self-efficacy and career direction clarity compared to students from broken homes. However, some adolescents from broken families showed positive resilience through the support of teachers and a supportive school environment. These findings reinforce the ecological development framework and Social Cognitive Career Theory, which emphasise that career development is the result of interactions between psychological factors and social contexts. Practically, this study recommends strengthening family-based career guidance and counselling in schools to help students cope with the psychological and social dynamics resulting from changes in family structure. These results are expected to contribute to the development of more inclusive educational models and counselling services that are sensitive to the family context in Indonesia.